Origins of The wheel of time : the legends and mythologies that inspired Robert Jordan - Livingston, Michael, 1975- (Tor, 2022)
"This companion to the internationally bestselling series will delve into the creation of Robert Jordan's masterpiece, drawing from interviews and an unprecedented examination of his unpublished notes. Michael Livingston tells the behind-the-scenes story of who Jordan was, how he worked, and why he holds such an important place in modern literature. The second part of the book is a glossary to the "real world" in The Wheel of Time. King Arthur is in The Wheel of Time. Merlin, too. But so are Alexander the Great and the Apollo Space Program, the Norse gods and Napoleon's greatest defeat-and so much more. Origins of The Wheel of Time will provide exciting knowledge and insights to both new and longtime fans looking to either expand their understanding of the series or unearth the real-life influences that Jordan utilized in his world building-all in one, accessible text"--